Multiple metastatic basal cell carcinoma with concurrent metastatic pleomorphic sarcoma in chronic lymphedema area: case report Carcinoma basocelular múltiplo e metastático concomitante a sarcoma pleomórfico e metástatico em área de linfedema crônico: relato de caso - Giuliano da Paz Oliveira; Régio José Santiago Girão; Cléverson Teixeira Soares; Edgard Jose Franco Mello Junior (Sociedade Brasileira de Dermatologia, 2012)
Chronic lymphedema presents as interstitial fluid retention due to a failure in the lymphatic system drainage. The affected region becomes more vulnerable immunologically and predisposed to the onset of neoplasms. Basal Cell Carcinoma is the most common sort of neoplasm, nevertheless it rarely metastisizes. Sarcomas are malignant mesenchymal neoplasms, locally aggressive, which can spread. Here is reported an infrequent case of multiple basal cell carcinoma, synchronous to a poorly differentiated pleomorphic sarcoma, both spreading to lymph nodes and arising from tissue compromised by chronic lymphedema. Linfedema crônico se manifesta pelo acúmulo de líquido intersticial por falha da drenagem linfática. A região afetada torna-se imunologicamente vulnerável e predisposta ao desenvolvimento de neoplasias. Carcinoma basocelular é a neoplasia maligna mais comum, entretanto raramente metastatiza. Sarcomas são neoplasias mesenquimais malignas, localmente agressivas e capazes de metastatizar. Apresentamos um caso raro de múltiplos carcinomas basocelulares concomitantes a sarcoma pleomórfico pouco diferenciado, metastáticos para linfonodos, originando-se em área de linfedema crônico.